2003 International Conference on Multimedia and Expo. ICME '03. Proceedings (Cat. No.03TH8698) 2003
DOI: 10.1109/icme.2003.1220951
|View full text |Cite
|
Sign up to set email alerts
|

Detecting cartoons: a case study in automatic video-genre classification

Abstract: This paper presents a new approach for classifying individual video frames as being a 'cartoon' or a 'photographic image'. The task arose from experiments performed at the TREC-2002 video retrieval benchmark: 'cartoons' are returned unexpectedly at high ranks even if the query gave only 'photographic' image examples. Distinguishing between the two genres has proved difficult because of their large intra-class variation. In addition to image descriptors used in prior cartoon-classification work, we introduce no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…In the prior works, several classification systems based on different types of image features have been developed. In [1] the classification problem was addressed by modeling the characteristics of cartoon. The features are extracted from the color saturation, color histogram, edge histogram, compression ratio, pattern spectrum and the ratio of image pixels with brightness greater than a threshold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the prior works, several classification systems based on different types of image features have been developed. In [1] the classification problem was addressed by modeling the characteristics of cartoon. The features are extracted from the color saturation, color histogram, edge histogram, compression ratio, pattern spectrum and the ratio of image pixels with brightness greater than a threshold.…”
Section: Introductionmentioning
confidence: 99%
“…In [3], the joint spatial-color patch statistics, fractal geometry and differential geometry are formed in RGB space. In [1], some features are collected in HSV (Hue, Saturation, Value (brightness)) color space. In this paper, the proposed method constructs all features in the HSV color space.…”
Section: Introductionmentioning
confidence: 99%
“…Simple visual descriptors have been proposed to identify nonphotorealistic computer graphics [1,36,72,26,6]. For example, Ianeva et al [26] observed that the cartoonist graphics has characteristics of saturated and uniform colors, strong and distinct lines, and limited number of colors. They devised a computer graphics detection method that used image features such as the average color saturation, the ratio of image pixels with brightness greater than a threshold, the Hue-Saturation-Value (HSV) color histogram, the edge orientation and strength histogram, the compression ratio, and the distribution of image region sizes.…”
Section: Methods Using Visual Descriptorsmentioning
confidence: 99%
“…We compare the 192D geometry feature against the 216D wavelet feature [7] and the 108D feature obtained from modelling the characteristics of the general (i.e., including both photorealistic and non-photorealistic) computer graphics [5] (henceforth the cartoon feature). For a fair comparison, we compute the wavelet feature on the entire image (for a better performance), rather than just on the central 256×256-pixel region of an image, as described in [7].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Despite the fact that classification of photographic images and computer graphics has been applied for improving the image and video retrieval performance [5,13], classification of photographic images (PIM) and photorealistic computer graphics (PRCG) is a new problem. The work in [7] takes advantage of the wavelet-based natural image statistics, and extract the first four order statistics of the in-subband coefficients and those of the cross-subband coefficient prediction errors as features for classifying PIM and PRCG.…”
Section: Introductionmentioning
confidence: 99%